Le rôle des coopératives dans la diffusion d’une éco-innovation : le cas de l’adoption de films recyclés par les maraîchers du bassin nantais - Anne Musson; Damien Rousselière (Développement Durable et Territoires)
Our study is part of a research project called Smart, which focuses on the implementation of a circular economy system based on an environmental innovation : semi-forging plastic films made of recycled plastic. Preliminary work has identified a distrustful attitude from market gardeners towards change and a low consideration of environmental issues. These two facts constitute major barrier to the dissemination of an innovation. Our survey of experts underlines that agricultural producers have more confidence in producer organizations and cooperatives than in suppliers and/or other actors, which would make it possible to remove both the barrier of mistrust towards a new product and the lack of consideration of the environmental issue. Our contribution to the literature focuses on the positive role of collective organizations in disseminating eco-innovation in the presence of socio-technical lock-in of agricultural commodity chains.